Pengembangan Sistem Informasi Pengukuran Kualitas Layanan Akademik Berbasis Web - Aris Nurbawani (Jurnal SITECH : Sistem Informasi dan Teknologi, 2026)
Measuring academic service quality is a crucial component of higher education quality assurance systems. The Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo has used Google Forms for surveys; however, this approach presents limitations in reporting, data processing customization, and real-time information delivery for institutional leaders. This study aims to develop and analyze the quality of a Web-Based Academic Service Quality Measurement Information System (SIPKLA-Web) as a more effective, efficient, and integrated solution. This research adopts a Research and Development (R&D) approach using the waterfall model, consisting of requirements analysis, design, implementation, and testing. The system was evaluated based on functional suitability, compatibility, and usability. The results show that SIPKLA-Web performs all intended functions, is compatible across various operating systems and browsers, and provides a stable and user-friendly experience. It also generates real-time questionnaire reports in both web and Excel formats, supporting faster academic decision-making. Usability analysis indicates scores of 88.49% (Usefulness), 89.29% (Ease of Use), 90.08% (Ease of Learning), 89.68% (Satisfaction), and an overall usability score of 89.38%.